HUBUNGAN ANTARA INTERAKSI TEMAN SEBAYA DENGAN MINAT BELAJAR SISWA KELAS IV DI SDN 14 KOTO BARU - Agus Saputra; yulia Darniyanti; Desri Erita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Peer interaction plays an important role in shaping students' learning interest. This study was motivated by differences in students' learning interest between morning and afternoon sessions, particularly concerning the Tahfidz Al-Qur’an extracurricular activity, which is not mandatory. In Grade IV SDN 14 Koto Baru, some students participate while others do not, leading to a decline in learning interest among those whose friends are absent from the classroom.This research aims to analyze the relationship between peer interaction and students' learning interest using a quantitative correlational method. The population and sample consist of 30 students using a saturated sampling technique. Data were collected through questionnaires and documents, tested for validity with 16 items per variable, and reliability using Cronbach’s Alpha (0.760 for peer interaction and 0.691 for learning interest). Normality tests using Shapiro-Wilk show normal distribution (0.632 and 0.078). Linearity testing resulted in 0.237, indicating a linear relationship. Hypothesis testing using simple linear regression shows a significance value of 0.006 (<0.05), confirming that peer interaction influences students' learning interest. The effective contribution of peer interaction is 23.7%, while 76.3% is influenced by other variables.